The Stability Analysis of Roadway near Faults under Complex High Stress - Biao Zhang; Huaqiang Zhou; Qingliang Chang; Xu Zhao; Yuantian Sun (Advances in Civil Engineering)
Based on geological conditions of 3318 working face haulage roadway in Xuchang Coal Mine, as well as the space-time relationship with surrounding gob, theoretical analysis and numerical simulation were used to study the influence of fault structure on the original rock stress of 3318 working face transport roadway. Considering the composite action of the leading supporting pressure of 3318 working face and the structure and the lateral supporting pressure of gob, the stress distribution and deformation law of roadway under the complex and high-stress condition are studied. The results show that, under the superposition of lateral abutment pressure of goaf and abutment pressure of adjacent working face and fault structure, the peak stress of roadway roof and floor moves to the surface of roadway surrounding rock, and its distribution law changes from obvious symmetry to asymmetry; surrounding rock on both sides of roadway forms asymmetric circular concentrated stress area; roof and floor and two sides of roadway show asymmetric characteristics. This reveals the stability characteristics of roadway surrounding rock under the action of multiple perturbation stresses.